Analisis Kajian Stuktural Pada Cerpen “Kembang Mayang” Karya Titie Said - Mirabella Husen Asgaf; Lusi Nur Triani (BADAN PENERBIT STIEPARI PRESS, 2024)
The short story Kembang Mayang has a theme centered around women's emancipation. It follows a forward plot, although there is a brief flashback in the middle of the story. However, the flashback does not affect the overall storyline; it merely strengthens it. The main character in Kembang Mayang is Eka. The characters of Eka’s mother, father, Mulyo, and his seven younger siblings are secondary characters who primarily serve as supporting elements to the story. Eka is portrayed as a tough, responsible, and loving individual. The story takes place in the early morning before dawn in a house in Ciganjur. The author uses the third-person point of view, not using the pronoun